A construção do pan-americanismo na revista em guarda: o olhar norte-americano pela defesa das Américas (1941-1946) - SILVA, Julio Cesar dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
O presente artigo discorre sobre o período de divulgação da revista Em Guarda (1941-1946). No decorrer de sua publicação, os norte-americanos apareciam como modelo de sociedade (político, cultural e social), enquanto aos latino-americanos cabia o papel de fornecer matérias-primas para a fabricação de produtos voltados à guerra. Pretendo discutir as estratégias adotadas pelo mensário na construção do discurso de união interamericana sob a ótica dos Estados Unidos. Desse modo, surgem novas possibilidades para o estudo das relações entre Brasil- Estados Unidos, em particular do pan-americanismo.

This article discusses the American magazine Em Guarda (1941-1946), during its publication the USA appeared as a model of society (political, cultural and social), while to the Latin Americans it was given the role of providing raw materials to manufactured products useful to the war effort. I want to discuss the strategies adopted by the monthly magazine in the construction of the discourse of Inter-American union from the perspective of the United States. Thus, we foresee new possibilities for the study of relations between Brazil and the United States, mainly the American view of Pan-Americanism.
The construction of the pan american magazine em guarda: looking for “american defense” of the americas (1941-1946)
Keywords: Pan-Americanism; Latin America; Press; Pan-Americanismo; América Latina; Imprensa